2011
DOI: 10.3109/17477166.2010.541463
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity prevalence and body mass index trends in Indian children

Abstract: The rising trend of BMI in Indian children and adolescents observed in this multicentric study rings alarm bells in terms of associated adverse health consequences in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
77
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 19 publications
12
77
6
1
Order By: Relevance
“…The result similar to as reported by Khadilkar et al 16 Prevalence of obesity among male 17(20.2%) was slightly higher vs. female 16(15.4%) but statistically not significant and similar to the result reported by Khadilkar et al 12.4 vs 9.9%, Harish Ranjani et al, and Sidhu et al 5 vs 6 %. 9,16,17 There was statistically significant difference (p <0.001) between urban and rural groups for the distribution of BMI categories A and B.…”
Section: Discussionsupporting
confidence: 81%
“…The result similar to as reported by Khadilkar et al 16 Prevalence of obesity among male 17(20.2%) was slightly higher vs. female 16(15.4%) but statistically not significant and similar to the result reported by Khadilkar et al 12.4 vs 9.9%, Harish Ranjani et al, and Sidhu et al 5 vs 6 %. 9,16,17 There was statistically significant difference (p <0.001) between urban and rural groups for the distribution of BMI categories A and B.…”
Section: Discussionsupporting
confidence: 81%
“…The growth references used in and obesity in children have shown that not only is there a rise in the incidence of overweight and obesity but adiposity rebound is seen at a younger age [5]. The pattern of growth in children has thus changed and hence we urgently need to update Indian growth charts.…”
mentioning
confidence: 99%
“…For example, in China, the prevalence of overweight and obesity among children aged 7-9 yr increased from 1-2 per cent in 1985 to 17 per cent among girls and 25 per cent among boys in 2000 (9) . In the SEARCH study (10) the incidence rate (per 100,000 personyear) of type 2 diabetes among children and adolescents varies greatly by ethnicity, with the highest rates observed among youths aged [15][16][17][18][19] years in minority populations. In particular, the reported incidence rate was 49.4 for Native Americans, 22.7 for Asian/Pacific Islanders, 19.4 for African Americans, 17 for Hispanics, and 5.6 for non-Hispanic whites.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the reported incidence rate was 49.4 for Native Americans, 22.7 for Asian/Pacific Islanders, 19.4 for African Americans, 17 for Hispanics, and 5.6 for non-Hispanic whites. Most of the earlier studies done in children and adolescents in India have reported prevalence based on international cut-off points (11)(12)(13)(14)(15)(16)(17)(18)(19) , with a meta-analysis estimating the prevalence of overweight as 12.6% and obesity as 3.4% (20). Another multi centric study reported an overall prevalence of overweight/ obesity as 18.2%.…”
Section: Introductionmentioning
confidence: 99%